KAJIAN KOMPETENSI MANAJERIAL DAN PENANGANAN KOMPETENSI PROFESIONAL DI LABORATORIUM IPA SMP NEGERI 17 MAKASSAR - Hadriyanti, Hadriyanti (JFT: Jurnal Fisika dan Terapannya, 2020)
This study examines the managerial and professional competences in the science laboratory of SMP Negeri 17 Makassar. Data obtained through direct observation in the science laboratory by identifying all science laboratory equipment (Chemistry, Physics and Biology). The data is documented one by one and identified in accordance with government regulation (Permen) No. 26 of 2008 concerning School Laboratory Management. The results obtained are that (1) the condition of the carrying capacity of human resources (HR) and laboratory infrastructure to support the facilitation of the Science (Science) learning process at SMP Negeri 17 Makassar shows that the carrying capacity of the facilities and infrastructure, especially the laboratory equipment, has met criteria but it needs to be completed according to the specified standards and the managerial process is still minimal and not well organized and the intensity of laboratory use is still classified as moderate; (2) the science laboratory management system in SMP Negeri 17 Makassar can be seen in the competence of the head of the science laboratory, namely the average value of the standard understanding of the competency of the head of the laboratory is in a good category, but the application to streamline laboratory management activities is not fully maximized and has not according to the achievement targets set.